Energy justice : re-balancing the trilemma of security, poverty and climate change - McCauley, Darren (Palgrave pivot., 2017)
This book re-conceptualizes energy justice as a unifying agenda for scholars and practitioners working on the issues faced in the trilemna of energy security, poverty and climate change. McCauley argues that justice should be central to the rebalancing of the global energy system and also provides an assessment of the key injustices in our global energy systems of production and consumption. Energy Justice develops a new innovative analytical framework underpinned by principles of justice designed for investigating unfairness and inequalities in energy availability, accessibility and sustainability. It applies this framework to fossil fuel and alternative low carbon energy systems with reference to multiple case studies throughout the world. McCauley also presents an energy justice roadmap that inspires new solutions to the energy trilemna. This includes how we redistribute the benefits and burdens of energy developments, how to engage the new energy 'prosumer' and how to recognise the unrepresented. This book will appeal to academics and students interested in issues of security and justice within global energy decision-making.